Novice Teachers’ Online Discussions of School-Based Scenarios About Immigrant Students - Adams, Brittany; Dussling, Tess; Y. Stevens, Elizabeth; C. Li, Sunny (Journal of Education and Learning Environments, 2025)
This study examined the discursive patterns of novice teachers as they engaged with, reflected on, and discussed school-based scenarios about immigrant students in an online, asynchronous course. The purpose of this graduate course was to examine culturally sustaining and critical pedagogies. Students completed various readings on multiple social identities. To reinforce theory to practice, students participated in scenario-based reflections. In these reflections they were asked to make connections to their own identities, consider biases, and brainstorm equitable outcomes. In the written reflections, researchers identified patterns related to avoidance and conflation. Participants used emotive language and personal connections to shield themselves from difficult conversations. They often did not discuss immigrant status as a factor in the scenarios and racialized social identities unrelated to race. While participants were able to recognize biased behaviors within singular incidents, they rarely connected those behaviors to the larger systems of oppression. This qualitative case study drew on written discussion posts from 19 early-career teachers enrolled in a graduate-level education course. Using discourse analysis and inductive coding, the research team identified key patterns and themes in participants’ written responses. Findings from this study offer insights related to novice teachers’ intentions and (mis)understandings when working with immigrant students and offer important implications.